Effect of RECK Gene Polymorphisms on Hepatocellular Carcinoma Susceptibility and Clinicopathologic Features - Chung, Tsung-Te (Public Library of Science, 2012)
BACKGROUND: The reversion-inducing-cysteine-rich protein with Kazal motifs (RECK) down-regulation has been confirmed in numerous human cancers and is clinically associated with metastasis. This study investigates the potential associations of RECK single-nucleotide polymorphisms (SNPs) with hepatocellular carcinoma (HCC) susceptibility and its clinicopathologic characteristics. METHODOLOGY/PRINCIPAL FINDINGS: A total of 135 HCC cancer patients and 501 cancer-free controls were analyzed for four RECK SNPs (rs10814325, rs16932912, rs11788747, and rs10972727) using real-time PCR and PCR-RFLP genotyping analysis. After adjusting for other co-variants, the individuals carrying RECK promoter rs10814325 inheriting at least one C allele had a 1.85-fold [95% confidence interval (CI), 1.03–3.36] risk of developing HCC compared to TT wild type carriers. The HCC patients, who carried rs11788747 with at least one G allele, had a higher distant metastasis risk than wild type probands. CONCLUSIONS: RECK gene polymorphisms might be a risk factor increasing HCC susceptibility and distant metastasis in Taiwan.